Feasibility of using fallen tea leaves as litter in broiler rearing (Bangladesh Journal of Animal Science, 2012)
One hundred eighty straight run day old Cobb-500 broilers were reared on rice husk, sawdust, wood shaving and chopped tea leaves litter up to 35 days of age. The broilers were fed ad libitum. At 35 days the body weight of chicken reared on sawdust attained the highest body weight (p